Correction: Genetic differentiation at extreme latitudes in the socially plastic sweat bee Halictus rubicundus - Michels, Bas A.; Beekman, Mariska M.; Field, Jeremy; Gruber, Jodie; Pannebakker, Bart A.; Savill, Charlotte; Boulton, Rebecca A. (PLOS ONE, 2025)
null